PERLINDUNGAN MEREK TERDAFTAR TERHADAP PELANGGARAN DI MARKETPLACE DIGITAL DI INDONESIA - Narayana Khamil; Muhammad Haikal Wahyudi; Muhammad Humam Hikmah Nurwahid; Muhammad Rafly Alamsyah; Muhamad Pandu Septi Wiguna (Journal of Indonesian Comparative of Syari'ah Law, 2025)
The rapid development of digital technology has transformed trade transaction patterns, particularly through marketplace platforms. However, this phenomenon also presents challenges to the legal protection of registered trademarks, especially regarding infringements committed by irresponsible parties. This study aims to examine the concept and legal basis of trademark protection in Indonesia, identify the various forms of trademark infringement occurring in digital marketplaces, and analyze the liability of marketplace operators for infringements committed on their platforms. In addition, this research discusses the legal remedies and dispute resolution mechanisms available to trademark owners. The research method employed is normative juridical with a qualitative approach, based on an analysis of legislation and secondary sources such as journals, books, and official websites. The findings of this study indicate that the trademark protection system in Indonesia, particularly through the implementation of Law Number 20 of 2016 concerning Trademarks and Geographical Indications, provides a strong legal foundation for trademark owners to enforce their rights. Nevertheless, the effectiveness of such protection largely depends on the awareness, active participation of trademark owners, and the responsibility of marketplace operators in preventing and addressing infringements within the digital sphere.